Pantangan Makanan pada Suku Muyu di Papua - Agung Dwi Laksono; Ratna Dwi Wulandari (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2021)
ABSTRACT Background: Food for the Muyu tribe was an actualization of daily life over the belief in the religious dimension that is adopted and lived. This study aims to explore the food taboo among the Muyu tribe in Indonesia.Methods: The authors conducted the case study in Mindiptana, Boven Digoel, Papua. The study carried out data collection by participatory observation, in-depth interviews, and document searches. The authors carried out the report using an ethnographic approach an emically perspective.Results: Belief in the lord of wild animals, the lord of fruits and plants, and the lord of sago, was so thick that many spells appear to hunt and search for food in the forest, which was a form of recognition of the power of these. The Muyu tribe had restrictions on several types of food. Food can be taboo based on its physical form; meanwhile, because of Muyu people's belief that there was a bad quality inherent in these food ingredients. It was especially closely related to ritual practice for men as a process of undergoing initiation as a big man. The Muyu intended women taboo for mothers who are pregnant and breastfeeding. Abstinence for pregnant Muyu women was often related to the fetus in the womb. For children, especially for boys, it was almost the same as abstinence for adult Muyu men. This abstinence applies to boys who were prepared to be tómkót, especially when undergoing the initiation process.Conclusions: The food taboo applies to all Muyu people, both men, women, and children.